2013
DOI: 10.3926/jotse.51
|View full text |Cite
|
Sign up to set email alerts
|

Ethics in engineering: Student perceptions and their professional identity development

Abstract: Professional ethics instruction in engineering is commonly conducted by examining case studies in light of the code of conduct of a suitable professional body. Although graphical presentations of spectacular failures, sobering stories of the repercussions and the solid framework provided by the tenets of a code of ethics may leave a lasting impression, students generally gain their professional identity from relatives and colleagues. Their professional ethics tend to be mostly an extension of their personal et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 12 publications
(15 reference statements)
1
36
1
4
Order By: Relevance
“…It is also of concern that Ethical conduct and professional accountability elicited just 8% of the total responses across both international and domestic cohorts when identifying characteristics of an engineer (Figure 2) or perceived learning outcomes (Figure 7). This aligns with Stappenbelt's (2013) finding that engineering undergraduates lack awareness of aspects of professional ethics, and implies that education programs in engineering need to enhance student consciousness in this area.…”
Section: Differencessupporting
confidence: 71%
“…It is also of concern that Ethical conduct and professional accountability elicited just 8% of the total responses across both international and domestic cohorts when identifying characteristics of an engineer (Figure 2) or perceived learning outcomes (Figure 7). This aligns with Stappenbelt's (2013) finding that engineering undergraduates lack awareness of aspects of professional ethics, and implies that education programs in engineering need to enhance student consciousness in this area.…”
Section: Differencessupporting
confidence: 71%
“…A three year study conducted by Stappenbelt [12] involving a sample of 1,136 first year engineering students revealed that almost a third of this sample did not believe that current practicing professional engineers act ethically and a similar percentage felt that it was unrealistic to expect this ethical behaviour among engineers. It is ironic to note that some of the engineering students from today might play a critical role in shaping and influencing the future economic market with their innovation and decision making skills.…”
Section: Teaching Engineering Ethics In Higher Educationmentioning
confidence: 99%
“…It is ironic to note that some of the engineering students from today might play a critical role in shaping and influencing the future economic market with their innovation and decision making skills. Stappenbelt [12] labelled his findings as alarming and recommended that more work should be done to facilitate and encourage Engineering Ethics Education and shape students' professional identities. This is one of the reasons why the familiarity and teaching of Ethics in engineering practices is highly emphasized among engineering students in Higher Education.…”
Section: Teaching Engineering Ethics In Higher Educationmentioning
confidence: 99%
“…Additionally, he found that less than half of students responded in the affirmative to questions regarding their own or that of practicing engineers' adherence to the IEAust Code of Ethics, as well as to the question concerning the expectation that professional engineers abide by the IEAust Code of Conduct at all times. 17 Along similar lines, Kuczenski sought to determine rates of unethical behavior among engineering students, comparing students from three different institutions. "Unethical behavior" in her study refers primarily to forms of dishonesty, for example, cheating on an exam or copying a homework assignment.…”
Section: Introductionmentioning
confidence: 99%